Analysis Of Students' Critical Thinking Skills in Fifth Grade Science Learning at Sawunggaling Public Elementary School - Aminatul Mardiyah; Yuli Widiyono; Nurhidayati (PGMI IAIN Lhokseumawe, 2025)
Education is a deliberate process designed to create a learning environment that facilitates students’ development. This study aims to describe the critical thinking skills of fifth grade students in science learning and the factors that influence them. Critical thinking skills are the ability to think using HOTS to analyze, interpret, evaluate, summarize, and combine various information to solve a problem wisely. Science is a scientific study that discusses living things and their interactions with the environment and the universe. The type of research used in this study is descriptive qualitative. The subjects of this study were seven students of Sawunggaling Public Elementary School. Data collection techniques in this study used test, observation, interview, and documentation methods. Data analysis techniques in this study used data analysis according to Milles and Huberman. The results showed that the subjects wo were fifth grade students at Sawunggaling Public Elementary School were able to demonstrate critical thinking skills in the good category. Critical thinking skills in the very good category were achieved by subjects S1, S2, S3, S6, and S7. Critical thinking skills in the good category were achieved by subjects S5. Critical thinking skills in the sufficient category were achieved by subjects S4. Students’ critical thinking abilities are influenced by several factors such as internal and external factors.